2008
DOI: 10.1029/2007jg000623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Mg/Ca ratios as a temperature proxy in the estuarine oyster, Crassostrea virginica

Abstract: [1] We examined the potential utility of Mg/Ca SHELL ratios recorded in shells of the estuarine oyster Crassostrea virginica as a temperature proxy because oxygen isotope ratios (d 18 O) in estuaries are complicated by the simultaneous fluctuation in temperature and salinity, whereas Mg/Ca WATER ratios are assumed to be constant above 10 practical salinity units (psu). We tested this assumption and observed a slight mixing effect between 10 psu and normal marine values emphasizing the need to test this assumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 36 publications
8
77
0
Order By: Relevance
“…8A) are within the range of values reported in the literature for modern oysters (Surge and Lohmann 2008;Wisshak et al 2009), and the covariant trends observed for Mg/Ca vs. Sr/ Ca for the O. edulis var. lamellosa samples may indicate that there is a temperature effect on the Mg and Sr uptake (Surge and Lohmann 2008).…”
Section: Diagenesissupporting
confidence: 68%
See 2 more Smart Citations
“…8A) are within the range of values reported in the literature for modern oysters (Surge and Lohmann 2008;Wisshak et al 2009), and the covariant trends observed for Mg/Ca vs. Sr/ Ca for the O. edulis var. lamellosa samples may indicate that there is a temperature effect on the Mg and Sr uptake (Surge and Lohmann 2008).…”
Section: Diagenesissupporting
confidence: 68%
“…8A) are within the range of values reported in the literature for modern oysters (Surge and Lohmann 2008;Wisshak et al 2009), and the covariant trends observed for Mg/Ca vs. Sr/ Ca for the O. edulis var. lamellosa samples may indicate that there is a temperature effect on the Mg and Sr uptake (Surge and Lohmann 2008). We have no straightforward explanation for the higher Mg/Ca ratios of the oyster #1c-2 and #1a-1B and D samples, but we speculate that the increased ratios might reflect periods of increased metabolic activity (Rosenberg and Hughes 1991;Steuber 1999;cf.…”
Section: Diagenesissupporting
confidence: 68%
See 1 more Smart Citation
“…The Mg/Ca data also appear to show a diurnal cycle, but the amplitude is rather large and highly irregular. A few reports have described a positive correlation between the Mg/Ca ratio and temperature for Mytilus trossulus 24 and Crassostrea virginica 25 , although these earlier data were obtained using a conventional analytical method. There is a slight positive correlation between the Mg/Ca ratio and seawater temperature ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The partitioning of Mg/Ca between solid and liquid phases is thought to be temperature-dependent (Mucci 1987) and thus potentially tracks changes in ambient temperature acting as a palaeothermometer (Klein et al 1996). However, correlations between temperature and Mg/Ca can be weak with temperature reconstructions requiring precise knowledge of the environment during shell growth (Surge and Lohmann 2008), making Mg/Ca only suitable as an auxiliary proxy. Ratios of Sr/Ca have also been explored as a proxy for palaeotemperature (Freitas et al 2006); however, it was found that correlations were generally weak or inconsistent.…”
Section: Trace Element Analysismentioning
confidence: 99%